Simulation of structure of special tilt boundary and grainboundary self-diffusion in Ti - Popov, Vladimir; Urazaliev, Mihail; Stupak, Maksim (Diffusion Fundamentals, 2022)
Symmetric tilt boundary [2 110] (01 12) in HCP titanium has been investigated by computer simulation methods using the embedded atom potential. The structure and energies of the considered boundary and the energies of formation of vacancies in it have been calculated by the method of molecular-static simulation. The stability of the boundary at elevated temperatures has been investigated by the molecular dynamics method, and the coefficients of grain-boundary diffusion have been calculated.